Penerapan Algoritma AES 256 Pada Qr Code Untuk Sistem Registrasi Event Sepeda - Mohamad Dani Saputro; Binanda Wicaksana; Farhan Zayid (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
Technology and the digital era are currently developing rapidly and providing various conveniences for humans in various aspects, including in the field of event organizers. After the Covid-19 pandemic ended, events began to be held again in various areas, including in Bogor. Bicycle events are one of the events that are highly anticipated by bicycle hobbyists, but there are still many event organizers who depend on Google Forms as a place to register participants. The problems that occur in the registration system using the Google form are related to data management and the ineffectiveness and efficiency the registration process because according to the value the registration process used at this time is still quite convoluted, causing queues at the time of re-registration of participants. In addition, there is no security that can maintain the authenticity of participant data, because currently registration data that is input via Google Form is directly stored automatically on Google Drive where the Google Drive account can still be accessed together so that leaks and tracing errors will be difficult to do. Therefore, the application of the AES 256 algorithm to the QR code is considered the right solution to increase system effectiveness, efficiency and security. registration. This research has carried out a feasibility test on a prototype that was built based on the evaluation value of the system which has been carried out through a questionnaire by 2 experts and 5 users showing that the system developed is very feasible with a percentage value of 84%. Thus, the use of the AES 256 algorithm on the QR code can be declared effective and efficient for increasing participant data security in the mountain bike event registration system.